Môže „teória brutalizácie“ vysvetliť výbuch násilia v období Ukrajinskej revolúcie (1917 – 1921)? - Глібіщук, Микола (My University, 2020)
The author of this study tries to analyze the possibility of using George Moss' "brutalization theory" to clarify the outbreak of violence during the Ukrainian Revolution (1917–1921). After researching each part of this theoretical concept, the author claims that it does not fit into the Ukrainian case. The author's arguments prove that this construct, built on the Western European narrative, cannot be used to understand the causes of violence during the Ukrainian Revolution
Can the "brutalization theory" explain the outbreak of violence during the Ukrainian Revolution (1917–1921)?
Keywords: "brutalization theory", George Mosse, First World War, Ukrainian Revolution (1917–1921), violence.